Frecuencia de alveolitis según el protocolo quirúrgico de exodoncias en pacientes de la Clínica Integral de Adultos de la UNL, octubre 2017-marzo 2018. - Castillo Alberca, Víctor Manuel (2018)
The purpose of this study was to determine alveolitis frequency according to the surgical protocol of exodontias in patients of the Clínica Integral de Adultos (Holistic Care Clinic for Adults) of the Universidad Nacional of Loja, October 2017-March 2018. For this research, we took the patients who were directed to tooth extraction. Using observation forms, it was verified whether the surgeons achieved the surgical and biosafety procedures or not. The information analysis was carried out using Excel and Spss. The following results were obtained: from 87 teeth extracted, 10 presented alveolitis which represents 11.4% (5.7% for men and 5.7 for women). The type of alveolitis was dry in 60% of the cases. The most common ages of occurrence was 22-33 with a 6.89%. The most affected pieces were the upper molars with a 4.59%. When establishing the relation with the surgeon biosafety: because of incorrect hands washing, there was 4.59% of alveolitis; lack of extraoral and intraoral asepsis, in a 10.3% and 11.4% of the cases alveolitis was evident, respectively. In relation with the surgery time, no significant difference was observed, except with the bandage placing, (11.4% was found) those who did not put it, got alveolitis in a 100% of the cases. In order to do the statistical analysis of the values square chi was used, which presents values under 0.05. This shows a relationship between the variables to be studied. Key words: Alveolitis, surgical protocol of exodontia.